Mismatch Negativity in Children: Reference Values - Ferreira,Dulce Azevedo (2019)
Abstract Introduction The Mismatch Negativity (MMN) auditory evoked potential evaluation is a promising procedure to assess objectively the ability of auditory discrimination. Objective To characterize the latency and amplitude values of MMN in children with normal auditory thresholds and without auditory complaints. Methods Children between 5 and 11 years old participated in the present study. All participants underwent acoustic immittance measurements and tonal and vocal audiometry. The MMN was recorded with the MASBE ATC Plus system (Contronic, Pelotas, RS, Brazil). The electrodes were fixed in Fz (active electrode), Fpz (ground electrode) and in M2 and M1 (references electrodes). The intensity used was 80 dBHL, the frequent stimulus was 1,000 Hz and the rare stimulus was 2,000 Hz. The stimuli were presented in both ears separately. Results For the female group, the mean latencies and amplitude of MMN were 177.3 ms and 5.01 μV in the right ear (RE) and 182.4ms and 5.39 μV in the left ear (LE). In the male group, themean latencies were 194.4 ms in the RE and 183.6ms in the LE, with an amplitude of 5.11 μV in the RE and 5.83 μV in the LE. There was no statistically significant difference between ears (p = 0.867 - latency and p = 0.178 - amplitude), age (p > 0.20) and the gender of the participants (p > 0.05). Conclusion Using the described protocol, the mean latency value of MMN was 184.0 ms for RE and 182.9 ms for LE, and the amplitude was 5.05 μV and 5.56 μV for the left and right ears, respective.